O5 Understanding continuing high hiv incidence: sexual behavioural trends among msm in london, 2000–2013. (18th May 2015) - Aghaizu, Adamma; Nardone, Anthony; Copas, Andrew; Mercey, Danielle; Wayal, Sonali; Parsons, Vicky; Hart, Graham; Gilson, Richard; Johnson, Anne
Abstract : Introduction: HIV incidence among men who have sex with men (MSM) has remained unchanged over the last decade despite increases in HIV testing and antiretroviral (ARV) coverage, suggesting sexual risk behaviours have increased. Aim: To examine trends in sexual behaviours among MSM and potential transmitters and acquirers of HIV. Methods: Ten serial cross-sectional surveys using self-completed questionnaires and HIV antibody testing among MSM in London gay social venues between 2000 and 2013. Results: Of 11, 876 MSM, 12.8% (n = 1494) were HIV+ of whom 34% (n = 513) were undiagnosed. The proportion reporting unprotected anal intercourse (UAI) the previous year increased from 43.2% (513/1187) in 2000 to 52.6% (394/749) in 2013 (p < 0.001); serosorting increased from 21.4% (242/1132) to 32.6% (208/639) (p < 0.001). One in 20 (4.6%, n = 527) were at risk of transmitting HIV (defined as undiagnosed MSM reporting UAI or diagnosed MSM reporting UAI and not exclusively serosorting). Over the period, their median number of UAI partners increased from 2 (IQR1, 10) to 10 (IQR2, 20) compared to from 0 (IQR0, 1) to 1 (IQR 0, 1) among other MSM. One in four (25.4%, 2633/10364) were at risk of acquiring HIV (defined as HIV – MSM reporting ≥1casual UAI partner in the previous year or not exclusively serosorting with any partner type). Discussion/conclusion: Between 2000 and 2013, the proportion of MSM reporting recent UAI increased, as has serosorting. We found a core group of MSM at risk of transmitting or acquiring HIV, the former with increasing UAI partner numbers. This may explain the sustained HIV incidence over the decade.